Tecnologias da informação e comunicação e educação: contradições na teoria e na prática no contexto da sociedade capitalista contemporânea - Ana Paula Batista de Oliveira (2014)
This study constitutes in a theoretical and practice analysis about the subject Information and Communication Technologies (ICT) and education in the context of the contemporary capitalist society. For all practical purposes, we perform the analyzes of the results of the Research project, teaching and extension integration of Information and Communication Technologies in Teacher Education, who composed the Consolidation Program for Undergraduate (Prodocência - UFMG) articulated with the theoretical analyzes. The goal of this research, that now we presents its results, was to uncover the political and economic intentions of the use of ICT in the contemporary capitalist society, in education; mainly analyze how technology was being appropriated by groups and dominant social classes; and the importance of education and ICT for capitalism; contextualize the different elements that composes them, emphasizing the work and teacher education. Understand the training process of the undergraduates of the UFMG within the analyzed project. We present an analysis of conflicting uses of technology. On the one hand, their appropriation by the capitalist system, contributing to capital accumulation. On the other hand, your emancipatory possibilities in society and education. Paraphrasing István Mészáros, we consider that there is possibilities of use of ICT "beyond the Capital". We adopt, in qualitative research, a literature from references that conceptualize and analyze the technical, the technology and the education in contemporary times. For the quantitative data, we used the questionnaire as a methodological tool, and the analysis of assessments and self-assessments of teacher students of the elective course: Information Technologies and Communication and Education: Theories and Practices, subject which composes, as a guiding element, the project said. Through this survey, we confirm the predominance of the contradictions of ICTs both in theory, and in practice.